SISTEM INFORMASI AKADEMIK SMA N 1 ULUJAMI PEMALANG BERBASIS WEB (Information Technology and Telematics, 2015)
Absrtack. SMA Negeri 1 Ulujami Pemalang is secondary educational institutions in the district of Pemalang. Academic information system SMA 1 Ulujami Pemalang in data processing still using manual systems. The purpose of this research is to design, build academic information system SMA N 1 Ulujami Pemalang web based. Where to build a system using a system development tool that is Data Flow Diagrams (DFD), Context Diagram, Entity Relationship diagrams (ERD). As well as using the programming language PHP, and HTML, and MySQL. This research has produced the academic information system SMA N 1 Ulujami Pemalang which can produce web-based student data report, teacher data reports, student grade reports. Therefore we make the design of information systems using HTML and PHP programming language with a database is MySQL and Apache web server. Suggestions for improvement of research is the use of a database that is free for example MySQL as database addressable system so that it can save the cost of. Keywords : Academic Information System, DFD, MySQL, php